2017
DOI: 10.1148/rg.2017170059
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Pediatric Thyroid Nodules

Abstract: A thyroid nodule detected clinically or incidentally at medical imaging is a common indication for ultrasonography (US) in the adult population. This scenario is less frequently the case in pediatric patients, and the approach to evaluation of thyroid nodules deserves modification in these patients because of the increased probability of malignancy in children, compared with adults. Evaluating a thyroid nodule with US in a systematic way requires familiarity with a number of features that can be assessed and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 73 publications
(183 reference statements)
1
31
0
5
Order By: Relevance
“…In general, the US features most concerning for malignancy are hypoechogenicity, irregular margins, and increased intranodular blood flow, as well as the presence of microcalcifications and abnormal cervical lymph nodes. On the other hand, entirely cystic nodules are regarded as almost always benign [3,25,26].…”
Section: Ultrasonography (Us)mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the US features most concerning for malignancy are hypoechogenicity, irregular margins, and increased intranodular blood flow, as well as the presence of microcalcifications and abnormal cervical lymph nodes. On the other hand, entirely cystic nodules are regarded as almost always benign [3,25,26].…”
Section: Ultrasonography (Us)mentioning
confidence: 99%
“…Several studies have investigated the sonographic features of malignant pediatric thyroid nodules [8,[25][26][27][28][29]. In the largest and most detailed series, including 404 nodules in 314 children, Richman et al showed that most of the sonographic characteristics of a nodule associated with increased risk of cancer in adults also convey a higher risk of malignancy in children.…”
Section: Ultrasonography (Us)mentioning
confidence: 99%
“…e early detection of thyroid nodules in adult patients has contributed to the increased diagnosis of thyroid cancer and has improved the clinical outcomes in these patients [9,[11][12][13]. In pediatric thyroid nodule patients, the American yroid Association recommends ultrasonography (US) and fine needle aspiration (FNA) for the evaluation of thyroid nodules [14][15][16]. More accurate diagnoses of the nodules have, therefore, been made possible, although the number of unnecessary examinations of benign nodules has also increased [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Finally, no well-validated paediatric scoring scheme helping predict malignancy risk, akin to the ATA Adult US Risk Stratification Scheme or the Adult McGill Thyroid Nodule Score, exists. 4,5 Finally, no well-validated paediatric scoring scheme helping predict malignancy risk, akin to the ATA Adult US Risk Stratification Scheme or the Adult McGill Thyroid Nodule Score, exists.…”
mentioning
confidence: 99%
“…Secondly, though US features suspicious for malignancy are well known to be similar between children and adults, few large studies explore which subtle, paediatric-specific US findings most predict malignancy. 4,5 Finally, no well-validated paediatric scoring scheme helping predict malignancy risk, akin to the ATA Adult US Risk Stratification Scheme or the Adult McGill Thyroid Nodule Score, exists. 13,14 Having an adjunctive scoring tool to be used with FNA results may help providers improve both the diagnosis and management of paediatric thyroid nodules.…”
mentioning
confidence: 99%